2021
DOI: 10.3390/cells10081902
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Heteroreceptor Complexes and Their Integration of Signals in Neurons and Astroglia—Relevance for Mental Diseases

Abstract: The heteroreceptor complexes present a novel biological principle for signal integration. These complexes and their allosteric receptor–receptor interactions are bidirectional and novel targets for treatment of CNS diseases including mental diseases. The existence of D2R-5-HT2AR heterocomplexes can help explain the anti-schizophrenic effects of atypical antipsychotic drugs not only based on blockade of 5-HT2AR and of D2R in higher doses but also based on blocking the allosteric enhancement of D2R protomer sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 107 publications
(320 reference statements)
0
18
0
Order By: Relevance
“…These triads can contain both dopamine and serotonin or adrenergic terminals. The first point on how the interaction between DRs and 5-HT receptors can occur is the formation of the heteroreceptor complexes of D 2 DR and 5-HT 2A receptors [ 125 ]. The heterocomplexes could explain the effects of atypical antipsychotic drugs [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These triads can contain both dopamine and serotonin or adrenergic terminals. The first point on how the interaction between DRs and 5-HT receptors can occur is the formation of the heteroreceptor complexes of D 2 DR and 5-HT 2A receptors [ 125 ]. The heterocomplexes could explain the effects of atypical antipsychotic drugs [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first point on how the interaction between DRs and 5-HT receptors can occur is the formation of the heteroreceptor complexes of D 2 DR and 5-HT 2A receptors [ 125 ]. The heterocomplexes could explain the effects of atypical antipsychotic drugs [ 125 ]. One of the possible mechanisms is based on blocking the allosteric enhancement of D 2 DR protomer signaling by 5-HT 2A receptor protomer activation.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that the SSRIs might modulate increased serum IL-8 levels in patients with MDD. The SSRIs have been reported to modulate microglia and astrocytes in hippocampus to produce the inflammatory cytokines including IL-8 ( 69 73 ). Moreover, MDD has been considered a neuroinflammatory disorder that was implicated in the abnormal activities of brain microglia and astrocytes ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above, it has been observed that Gal (1–15) but not Gal (1–29) can modulate in an antagonistic way 5-HT1AR in the dorsal hippocampus. It was proposed that GalR1-GalR2-5-HT1AR receptor mosaics can exist in the hippocampus, on dorsal raphe cells, and other limbic neurons where galanin fragment 1–15 is also able to exert allosteric interactions via modulation of the GalR1-GalR2 component of the trimeric hetero receptor complex to enhance 5-HT1AR protomer function in the basal state of this heterocomplex [ 138 ].…”
Section: Receptor Homo and Heterodimerization With Relevance For Mddmentioning
confidence: 99%
“…It is of special interest that ketamine can have direct effects on the 5-HT2R and D2R, as observed in 2002 [ 385 ]. It will be of special interest to understand if the D2R-5-HT2A heterocomplex is especially vulnerable to ketamine treatment [ 131 , 135 , 138 ]. Presently the relevance of the high affinities of ketamine for D2R and 5-HT2R is not clear regarding the role of ketamine in mental disorders.…”
Section: Novel Therapeutic Strategies For Treatment Of Mdd and Anxiet...mentioning
confidence: 99%